Annotated Database Construction Framework for Partially Occluded Face Recognition - Shanmugavadivu, P; Kumar, A (International Journal of Computer Sciences and Engineering, 2025)
The need of face recognition exponentially progresses due to its applications in law and enforcement, commercial to security systems. The existing face recognition systems efficiently accomplish this task in the constrained environment. However, implementation of face recognition system in unconstrained environment still remains as a challenge. There major issues in unconstrained environment are facial expression, illumination and partial occlusion. The collection and collation of enormous individuals’ data such as profile images of employee of an organization or citizens of a province for the creation of public dataset itself is highly complex. This paper presents a generic framework to construct an annotated database, especially for the partially occluded face recognition system. This Annotated Database Construction Framework (ADCF) has the provision to store the profile images and the facial components, along with the respective feature vectors. This ADCF felicitates the logical calibration of database contents to address the need of Partially Occluded Face Recognition System, with reference to the probe image. Hence, ADCF offers better scope for the researcher to precisely validate the authenticity of any face recognition system even with occlusion